STUDENT ANALYSIS OF THE SCIENCE PRACTICAL DEMONSTRATION VIDEO AT SMP N 8 PADANG - Nada Muthiara Dhenil; Arief Muttaqiin (Pendidikan IPA, FMIPA, UNP, 2023)
The aim of this research is to analyze students’ knowledge, experience and interest regarding science practical demonstration videos, as well as students’ knowledge about critical thinking. Questionnaire was used to collec the data. Data analysis was carried out by the descriptive statistics. The research result show that 58% of students are interested in the video, 58% of students experience difficulties if they do not use practical videos in learning, 17% of students have already carried out practical work, 25% of students already know about practical demonstration videos and 92% of students are enthusiastic if teachers use these videos as learning media. From the aspect of students experience and knowledge about critical thinking, 8% of students have heard about critical thinking and 25% of students already know that critical thinking is. In the aspect of students’ interest in practical demonstration video, 83% of students are interested in learning using video demonstrations and 100% of students agree that the video contains a demonstrator, voice acting, animation, images, supporting text and backsound.